MEC-RHA: Demonstration of Novel Service Request Handling Algorithm for MEC - Dilanka, Gayan; Viranga, Lakshan; Pamudith, Rajitha; Gamage, Tharindu D.; Ranaweera, Pasika; Balapuwaduge, Indika A. M.; Liyanage, Madhusanka (IEEE/IFIP Network Operations and Management Symposium, 2022)
Multi-Access Edge Computing (MEC) is a cloud computing evolution that delivers end-user services at the mobile network's edge. As a result, MEC guarantees that users will benefit from ultra-low latency and increased bandwidth when using the services. The orchestration process is the holistic management and control of the edge computing platforms. Handling of service requests forwarded by the MEC subscribers is an inceptive function that requires the intervention of the orchestrator. This paper demonstrates how an advanced service request handler algorithm (MEC-RHA) works on MEC orchestration, considering factors of service priority levels, feasibility, and resource availability when launching a service; while an optimal MEC server selection process is formed based on those factors.